2019
DOI: 10.1038/s41467-019-09611-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping vaccination coverage to explore the effects of delivery mechanisms and inform vaccination strategies

Abstract: The success of vaccination programs depends largely on the mechanisms used in vaccine delivery. National immunization programs offer childhood vaccines through fixed and outreach services within the health system and often, additional supplementary immunization activities (SIAs) are undertaken to fill gaps and boost coverage. Here, we map predicted coverage at 1 × 1 km spatial resolution in five low- and middle-income countries to identify areas that are under-vaccinated via each delivery method using Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 41 publications
6
104
0
1
Order By: Relevance
“…There was a significant effect on both fully immunised status and DPT3 coverage up to more than two-hours. Observed lower odds of longer travel time on DPT3 compared to fully immunised status highlight a differential access problem since infants require three contacts with the health facility to receive DPT3 vaccine, which is typically delivered through stationary health posts unlike fully immunised status that is influenced by supplemental immunisation activities for measles and polio vaccines [ 63 ]. Across SSA, the effect of spatial access on immunisation uptake has been varied.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant effect on both fully immunised status and DPT3 coverage up to more than two-hours. Observed lower odds of longer travel time on DPT3 compared to fully immunised status highlight a differential access problem since infants require three contacts with the health facility to receive DPT3 vaccine, which is typically delivered through stationary health posts unlike fully immunised status that is influenced by supplemental immunisation activities for measles and polio vaccines [ 63 ]. Across SSA, the effect of spatial access on immunisation uptake has been varied.…”
Section: Discussionmentioning
confidence: 99%
“…The 2018 PMCCS confirmed that SIAs reach much higher coverage than routine in much of Nigeria and importantly, SIA coverage among previously MCV zero-dose children was high (27), suggesting that lack of acceptance of vaccination is not a major barrier. A mixedmethods study in two Nigerian states found that receipt of MCV was related to awareness of vaccination, parental education, maternal participation in decision-making, presence of a government vaccination facility, and lack of barriers such as having to pay for vaccination (48).…”
Section: Discussionmentioning
confidence: 80%
“…To compound the problem of low average coverage, Nigeria was recently ranked highest among 45 GAVIsupported countries for inequity in coverage (46,47) Crude coverage of MCV was higher than that of Penta3, and four states achieved over 80% coverage for measles. This probably reflects the inclusion of campaign doses in the measure of measles vaccination coverage (27), as about half the age cohort included in MICS-NICS would have been eligible for the 2015-16 measles SIA. This conclusion is supported by the finding that MCV coverage was slightly lower than Penta3 coverage among children with cards (where documented doses reflect RI) whereas it was about twice as high as Penta3 by recall (Table 1) and the low availability of HBR meant that most information was obtained by verbal recall, though some missed-opportunities to give Penta when a child present late for vaccination cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, there has been a limited number of research in DRC concerning vaccination dropout (36). To our knowledge, the present study is the rst conducted at both ne spatial scale and individual level to understand the main health concern of vaccine services and identify factors related to low vaccination completeness among children aged 12-23 months.…”
Section: Discussionmentioning
confidence: 98%